Investment and innovation activity in the conditions of globalization changes in the transport processes of the country - Popova, A. M.; Попова, А. М.; Попова, А. Н. (Харківський національний автомобільно-дорожній університет, 2019)
Рurpose of the study is to identify shortcomings in the work of the transport network and ways to overcome them. Methodology of research. To achieve this goal in scientific work the following general scientific and special methods and techniques of research were used: methods of generalization and integrated approach to clarify the theoretical issues of formation of the transport complex of the country, and levers of influence on the detection of deficiencies and defects in the transport system of the country. Findings. The conducted review of the current state of the transport complex of Ukraine makes it possible to conclude that the necessary changes and the use of new methods in the work to improve the level of competitiveness of services, in which new characteristics appeared, and therefore, the use of new market instruments that are needed both at the enterprise level and on the sectoral, transport system of the country as a whole. Thus, the use of new means in the transport system allows to solve several problems facing transport service providers, such as: removal of additional burdens from entrepreneurs in the form of losses during transportation by improving the quality of road cover and a set of measures to improve the quality of the routes and as a consequence of lower cost the final product (increasing the efficiency of production of goods and services), and for consumers of passenger transportation is an important economic affordability of transport young men giving some freedom of movement and availability of transportation services for all segments of the population. System changes in work and innovative implementation will not only improve the quality of services, but also get on the same level with European transport companies. So lowering the cost of services and improving their quality can be met by the needs of their own consumers in the country and provide additional foreign exchange earnings at the expense of international carriers, international cargo delivery services and passengers. All of these issues are multicomponent components of the formula for assessing the performance of Ukraine's motor transport, changes in which due to globalization changes in the world and the expansion of borders. Competitiveness in the European transport services market is so high that, in order to create the appropriate level of the national transport system, each component of a complex transport system is a factor affecting the efficiency of all system parameters. Originality. Based on transport development issues, a more comprehensive and complete definition of the issues arising in the transport complex and ways to overcome them in order to increase the competitiveness of the domestic transport system, as well as the possibility of attracting additional investment funds and the introduction of innovations both domestic and foreign. Practical value is precisely the effect on the above-mentioned factors with maximum efficiency, which will give a significant impetus to the development of the whole transport system of Ukraine as a whole and road transport, in particular, such as: traffic congestion in "peak periods" and uneven flows, coverage of highways and hard-surfaced roads (recently, an important issue of traffic in the summer was a significant increase in the temperature of the heavy-duty rolling stock) and other general issues nature and those that take into account the specifics of Ukrainian transport network.
Інвестиційна та інноваційна діяльність в умовах змін глобалізації у транспортних процесах країни
Инвестиционная и инновационная деятельность в условиях глобализационных изменений в транспортных процессах страны
Keywords: transport system; investments; innovations; international cooperation; rolling stock; infrastructure; транспортна система; інвестиції; інновації; міжнародне співробітництво; рухомий склад; інфраструктура; транспортная система; инвестиции; инновации; международное сотрудничество; подвижной состав; инфраструктура; 330.339; 10.30977/PPB.2226-8820.2019.22.0.4